Beyond the Last Touch: Attribution in Online Advertising - Berman, Ron (Marketing Science, 2018)
Online advertisers often utilize multiple publishers to deliver ads to multihoming consumers. These ads often generate externalities and their exposure is uncertain, impacting advertising effectiveness across publishers. We analyze the inefficiencies created by externalities and uncertainty when information is symmetric between advertisers and publishers, in contrast to most previous research that assumes information asymmetry. Although these inefficiencies cannot be resolved through publisher-side actions, attribution methods that measure campaign uncertainty can serve as alternative solutions to help advertisers adjust their strategies. Attribution creates a virtual competition between publishers, resulting in a team compensation problem. The equilibrium may potentially increase the aggressiveness of advertiser bidding, leading to increased advertiser profits. The popular last-touch method is shown to overincentivize ad exposures, often resulting in lower advertiser profits. The Shapley value achieves an increase in profits compared with the last-touch method. Popular publishers and those that appear early in the conversion funnel benefit the most from advertisers using last-touch attribution. The increase in advertiser profits comes at the expense of total publisher profits and often results in decreased ad allocation efficiency. We also find that the prices paid in the market will decrease when more sophisticated attribution methods are adopted. The online appendix is available at https://doi.org/10.1287/mksc.2018.1104 .